Spatial Evaluation Of The Accessibility And Suitability Of Urban Amenities: A Case Of Secondary Schools In Adama City, Ethiopia - Bisrat, Welegebrial (ASTU, 2022)
The achievement of equity in the distribution of urban public amenities is a main goal of paramount importance to urban planning. The allocation of schools in Ethiopian urban areas is mostly based on the population index, with little thought given to spatial accessibility and distribution patterns, which have an important implication for equitable service provision. There is a greater need for more schools as the population expands. Given the expense and challenges for both the initial implementation and any necessary future revisions, choosing the optimum site for a new school location is a difficult decision. This study aims to analyze the spatial distribution and accessibility of existing secondary schools in Adama City as of 2022 and to identify suitable sites for new secondary school development. The locations of secondary schools in the study area were spatially mapped. Location quotient and nearest neighbor analysis (NNA) were used to analyze the spatial concentration and spatial distribution pattern of the schools, respectively. The level of accessibility was assessed using the service area, which was calculated using the city's population density and road network distance. Through a literature study and expert interview, physical, environmental, and socioeconomic criteria for secondary school placement were identified. The suitability of the factors was standardized based on suitability rankings. An Analytical Hierarchy Process (AHP) was employed to determine the relative importance of each factor. Suitable sites were identified through weighted spatial overlay analysis in a GIS environment. The findings show that there is inequality of service provision between neighboring parts of the city, and the overall spatial distribution of the schools is found to be uneven and exhibits a clustered pattern. In addition 6.5% of the population is expected to travel more distances than the standard set to access secondary schools. Moreover, the results reveal that 3% and 17% of the study area are identified as highly suitable and moderately suitable for secondary school development, respectively. The study would support the planning of service provision, and it would also assist in formulating effective policies for the context. It would also give planners and stakeholders vital information regarding appropriate sites for the development of new secondary schools in the future in Adama City.
Keywords: Adama city AHP MCDA Geospatial technology spatial accessibility spatial distribution secondary school